Information (il)literacy - Lasić-Lazić, Jadranka; Dovedan Han, Zdravko; Kocijan, Kristina (2000)
In this paper, authors will research information literacy and illiteracy at the Faculty of Philosophy in Zagreb. In the reasearch, data obtained from all departments will be shown, and we shall try to find out differences in the quantity of information literacy and see what influences those differences. In addition to that, we shall show the amount of professors and students having information skills and, according to their opinion, how those skills improve the quality of work and learning process.
Projekt MZOS
Projekt MZOS
ENG